Interlibrary loan practices handbook - Weible, Cherié L.; Janke, Karen L. (American Library Association, 2011)
Consortia and other library partnerships are now sharing ever larger fractions of their collections, and this book gives library staff the tools necessary for a smoothly functioning ILL system.